Investigation of Physical and Mechanical Properties of Hybrid Polymer Composites (HPCs), Epoxy Resin Reinforced with PALF and Polyester Fiber - Bin Ahmad Husni, Ahmad Danial Syafiq; Wan Jusoh, Wan Amizah (Progress in Engineering Application and Technology, 2025)
Hybrid polymer composites are considered a new generation of advanced materials manufactured from natural and synthetic fibers to improve the physical and mechanical properties. The present paper discusses the properties of tensile strength for HPCs fabricated by laying layers of PALF and polyester mat fiber reinforcement with epoxy resin. The samples were fabricated through the hand lay-up process, while samples of one, two, and three layers of PALF-polyester were analyzed. Results have shown that the three-layer fiber had the best tensile strength and modulus of 22.54 MPa and 431.05 MPa, respectively. Moreover, SEM, XRD, and FTIR studies were done to confirm the structural advantages of hybrid composites. These results tend to indicate a great possibility for HPC in various sustainable applications within the construction sector.